Mechanical compression enhances ciliary beating through cytoskeleton remodeling in human nasal epithelial cells. (1st July 2021) - Lee, Seong Gyu; Lee, Sang-Nam; Baek, Junki; Yoon, Joo-Heon; Lee, Hyungsuk
Abstract: Nasal inflammatory diseases, including nasal polyps and acute/chronic sinusitis, are characterized by impaired mucociliary clearance and eventually inflammation and infection. Contact of nasal polyps with adjacent nasal mucosa or stagnated mucus within the maxillary sinus produces compressive mechanical stresses on the apical surface of epithelium which can induce cytoskeleton remodeling in epithelial cells. In this study, we hypothesized that compressive stress modulates ciliary beating by altering the mechanical properties of the cytoskeleton of ciliated cell basal bodies. For the primary human nasal epithelial cells, we found that the applied compressive stress higher than the critical value of 1.0 kPa increased the stroke speed of cilia leading to the enhancement of ciliary beating frequency and mucociliary transportability. Immunostained images of the cytoskeleton showed reorganization and compactness of the actin filaments in the presence of compressive stress. Analysis of beating trajectory with the computational modeling for ciliary beating revealed that the stroke speed of cilium increased as the relative elasticity to viscosity of the surrounding cytoskeleton increases. These results suggest that the compressive stress on epithelial cells increases the ciliary beating speed through cytoskeleton remodeling to prevent mucus stagnation at the early stage of airway obstruction. Our study provides an insight into the defensive mechanism of airway epithelium against pathological conditions. Statement of significance: Cilia dynamics of the nasal epithelium is critical for not only maintaining normal breathing but preventing inflammatory diseases. It has been shown that mechanical compressive stresses can alter the shape and phenotype of epithelial cells. However, the effect of compressive stress on cilia dynamics is unclear. In this study, we demonstrated that the oscillation speed of cilia in human nasal epithelial cells was increased by the applied compressive stress experimentally. The computational simulation revealed that the change of ciliary beating dynamics was attributed to the viscoelastic properties of the reorganized cytoskeleton in response to compressive stress. Our results will be beneficial in understanding the defensive mechanism of airway epithelium against pathological conditions. Graphical abstract: Image, graphical abstract